A new Ocellularia (lichenized Ascomycota: Graphidaceae) from New Zealand indicates small-scale differentiation of an Australasian species complex. Issue 3 (2nd July 2020) - Marshall, Andrew J.; Blanchon, Dan J.; Lücking, Robert; de Lange, Theo J.P.; de Lange, Peter J.
ABSTRACT: Ocellularia (Graphidaceae) is a genus of crustose lichens comprising c.200 species, four known from Australia and New Zealand. Based on recent collections from northern North Island, we describe a fifth species Ocellularia jacinda-arderniae, which is a member of the O. bicuspidata complex. This complex is characterised by peculiar, appendiculate ascospores and a psoromic acid chemistry. Two further undescribed species of this complex, one from North Island and one from South Island, are discussed but left undescribed pending further study. Based on our findings, we provide a revised assessment of New Zealand Ocellularia . Of the four species included in the most recent Flora of New Zealand Lichens from 2007, three do not belong in that genus and the identification of the fourth is incorrect; instead, the following four taxa are recognised: O. jacinda-arderniae, O. aff. dolichotata, O. aff. bicuspidata (a) (South Island; OTA 58820) and O. aff. bicuspidata (b) (North Island; UNITEC 10818). This leads to the somewhat unusual situation that a presumably known genus biota in New Zealand is entirely replaced by names of a new species and three provisional identifications. The following new combination is introduced: Schizotrema concentricum (Stirt.) Lücking comb. nov. In addition, the name Thelotrema manosporum (C. Knight.) Hellb. is given as the correct name for the New Zealand taxon previously identified as T. monosporum Nyl., and the name T. monosporoides Nyl. [syn.: O. monosporoides (Nyl.) Hale] is established as a taxonomic synonym of T. manosporum, leaving two New Zealand species of Thelotrema with large, brown ascospores, namely T. manosporum and T. saxatile C. Knight. The situation of the genus Ocellularia highlights the need for detailed taxonomic revision of understudied lichen groups in New Zealand, especially as these and related genera in the Graphidaceae are excellent indicators of forest health and can be used for monitoring purposes.